Effect of different loading low density polyethylene (LDPE) on thermal and mechanical properties of Tapioca starch-based plastic composite / Norin Zamiah Kassim Shaari, Mazlan Bairik and Junaidah Jai - Kassim Shaari, Norin Zamiah; Bairik, Mazlan; Jai, Junaidah (Universiti Teknologi MARA, 2020)
Effect of incorporating different loading of low densities polyethylene (LDPE) on the mechanical and thermal properties of the plastic composite made from tapioca starch was investigated. The compound formulation was done in the internal mixer and the lump produced was crushed. Then, the crushed sample was compressed to form a dumbbellshaped in a compression molding equipment, heated at 140o C. The sample was subsequently analyzed for tensile property, thermal stability and functional groups. Results show that the incorporation of LDPE improves thermal and mechanical stabilities of the plastic composite. However, too much LDPE causes lower ductility of the composites. LDPE-15 was found as the best formulation since it has moderate tensile strength with good elongation.